1992
DOI: 10.1007/bf00034182
|View full text |Cite
|
Sign up to set email alerts
|

Boundary integral equation fracture mechanics analysis of plane orthotropic bodies

Abstract: In this paper, a quick and efficient means of determining stress intensity factors, K~ and Kn, for cracks in generally orthotropic elastic bodies is presented using the numerical boundary integral equation (BIE) method. It is based on the use of quarter-point singular crack-tip elements in the quadratic isoparametric element formulation, similar to those commonly employed in the BIE fracture mechanics studies in isotropic elasticity. Analytical expressions which enable K~ and K u to be obtained directly from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…They used tractionsingular-quarter point elements to the computation of the stress intensity factors and the crack propagation angle in orthotropic materials. Tan and G a o [ 15,16] used quarter-point elements and introduced analytical expressions for the stress intensity factors in terms of the BEM computed tractions and displacements for solving problems of orthotropic and anisotropic materials.…”
Section: Introductionmentioning
confidence: 99%
“…They used tractionsingular-quarter point elements to the computation of the stress intensity factors and the crack propagation angle in orthotropic materials. Tan and G a o [ 15,16] used quarter-point elements and introduced analytical expressions for the stress intensity factors in terms of the BEM computed tractions and displacements for solving problems of orthotropic and anisotropic materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that the displacement formula involves additional computational effort as compared with the traction formula. Tan and Gao (1992a) also showed that the stress intensity factors obtained using the displacement formulas are significantly more sensitive to the size of the crack-tip elements used. The traction formula is more widely used and the stress intensity factors can be obtained directly from the computed nodal tractions.…”
Section: Quarter-point Crack-tip Element In Plane Orthotropic Bodiesmentioning
confidence: 96%
“…In order to obtain the variation of the tractions, the nodal shape functions associated with nodal tractions have to be multiplied by 1 r , where l is the length of the element. Details of this formulation have been presented by Tan and Gao (1992a), Martinez and Dominguez (1984), and Cruse and Wilson(1977). …”
Section: Quarter-point Crack-tip Element In Plane Orthotropic Bodiesmentioning
confidence: 99%
“…Boundary collocation method has been proved to be an effective computational tool and has been successfully applied to variety of crack problems of isotropic materials (Chen and Chen, 1981;Newman, 1976;Ukadgaonkar and Murali, 1991;Wang et.al, 2003) and anisotropic materials (Wang and Chang, 1994;Woo and Samson, 1993). Various methods like modified mapping collocation method (Bowie and Freese, 1972), boundary integral equations (Tan and Gao, 1992) and singular integral equation formulation (Ryan and Mall, 1989) are successfully applied to solve the problems of finite orthotropic lamina / laminates containing edge / central crack.…”
Section: Introductionmentioning
confidence: 99%